2020
DOI: 10.1111/1556-4029.14267
|View full text |Cite
|
Sign up to set email alerts
|

Results of the 2018 Rapid DNA Maturity Assessment

Abstract: Three commercially available integrated rapid DNA instruments were tested as a part of a rapid DNA maturity assessment in July of 2018. The assessment was conducted with sets of blinded single-source reference samples provided to participants for testing on the individual rapid platforms within their laboratories. The data were returned to the National Institute of Standards and Technology (NIST) for review and analysis. Both FBI-defined automated review (Rapid DNA Analysis) and manual review (Modified Rapid D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Though initially designed for use in a booking environment with reference buccal swabs, the technology could be expanded for use within the laboratory to expedite the processing of reference samples associated with criminal cases. In 2019, the FBI conducted an internal validation study to this end (data not included) and found that the system, in accordance with what has been previously reported [1], performed at an approximate 85 % success rate. Success, for the purposes of this study, is defined as a profile for which at least the 20 core CODIS loci are detected and correctly assigned by the expert system software [2].…”
Section: Introductionsupporting
confidence: 61%
“…Though initially designed for use in a booking environment with reference buccal swabs, the technology could be expanded for use within the laboratory to expedite the processing of reference samples associated with criminal cases. In 2019, the FBI conducted an internal validation study to this end (data not included) and found that the system, in accordance with what has been previously reported [1], performed at an approximate 85 % success rate. Success, for the purposes of this study, is defined as a profile for which at least the 20 core CODIS loci are detected and correctly assigned by the expert system software [2].…”
Section: Introductionsupporting
confidence: 61%
“…For actual individual identification, statistical analysis should be performed for each gene peak. However, in this study, the number of samples to be confirmed was not large enough for a statistical approach, and the general approach of simply counting the number of matching loci was able to distinguish them from each other [ 27 ]. The urine and gargle fluid samples provided a full profile that could identify individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the above results showed a concordance rate of approximately 80% or more, the STR analysis is the best test for human-derived samples. However, only human genetic information can be obtained, and additional environmental or circumstantial information cannot be completely obtained [ 27 ]. As with human DNA, there are no specific marker loci such as STR.…”
Section: Discussionmentioning
confidence: 99%
“…The other is the Applied Biosystems RapidHIT ID System (Thermo Fisher Scientific, Waltham, MA, USA), which was formerly a product of IntegenX (Pleasanton, CA, USA) [ 42 46 ]. Previous changes/updates to the RapidHIT ID System instrumentation are the use of different PCR STR typing kits [ 22 24 ] and a single sample analysis design [ 14 , 22 ]. In the past few years, the RapidHIT ID instrument has been modified again compared with the previous versions.…”
Section: Introductionmentioning
confidence: 99%